Novel approach to intraoral haemorrhage after mandibular arteriovenous malformation embolization: transoral Onyx embolization of the posterior alveolar vein. (3rd July 2019) - Sozio, S.J.; Ngo, G.; Girgis, P.; Gupta, G.; Roychowdhury, S.
Abstract: Arteriovenous Malformation (AVM) of the mandible is a potentially life‐threatening condition that requires rapid diagnosis and intervention to prevent mortality or permanent morbidity 1 . While transarterial embolization using liquid embolic material currently serves as the mainstay of treatment, these lesions often feature complex internal anatomy, which may complicate this approach 2‐4 . This article presents the experiences of two patients who suffered significant intraoral haemorrhage secondary to the posterior alveolar draining vein of a complex mandibular AVM. In both instances, haemostasis was successfully achieved utilizing fluoroscopy‐guided direct puncture of the affected vessel through the oral mucosa, with subsequent Onyx® embolization.